2018
DOI: 10.1155/2018/4151692
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Root Canal Transportation by Three NiTi Single-File Systems in Curved Canals: A Cone Beam Computed Tomography Study

Abstract: Introduction This study is aimed at evaluating root canal transportation in the mesiobuccal canal of mandibular first molars prepared with One Shape, Reciproc, and M-One nickel titanium (NiTi) single-file rotary systems using cone beam computed tomography (CBCT). Materials and Methods In this ex vivo study, CBCT scans of 45 extracted human mandibular first molars with 20–40° curvature were obtained. The teeth were randomly divided into three groups (n=15) for preparation of the mesiobuccal canal with One Shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Centering ability was evaluated as described by Gambill et al 18 , who defines centering ability as the ability of the endodontic instrument to remain on the central axis of the root canal. In the present study, no significant difference was observed in centering ability between experimental groups, which is in line with other studies 12 , 28 . Although our study showed similar shaping ability in general results, when each section was analyzed separately, WOG file had less transportation than the MTwo instrument at the 5 mm section from the apex, which partially rejects the second hypothesis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Centering ability was evaluated as described by Gambill et al 18 , who defines centering ability as the ability of the endodontic instrument to remain on the central axis of the root canal. In the present study, no significant difference was observed in centering ability between experimental groups, which is in line with other studies 12 , 28 . Although our study showed similar shaping ability in general results, when each section was analyzed separately, WOG file had less transportation than the MTwo instrument at the 5 mm section from the apex, which partially rejects the second hypothesis.…”
Section: Discussionsupporting
confidence: 93%
“…Centering ability was evaluated as described by Gambill et al 18 , who defines centering ability as the ability of the endodontic instrument to remain on the central axis of the root canal. In the present study, no significant difference was observed in centering ability between experimental groups, which is in line with other studies 12,28 .…”
Section: Discussionsupporting
confidence: 93%
“…Canal transplantation results from the proclivity of the file to flatten and get back to its initial regular form while preparing the inclined root canal, which means removal of dentine completely from the outer surface of the curvature in the apical part of the canal. 16 SMI should be considering for suitable preparation to root canal anatomy that includes a measurement of root convexity in three- dimensional structure. 17 …”
Section: Introductionmentioning
confidence: 99%